Phylogenomic evidence for a recent and rapid radiation of lizards in the Patagonian Liolaemus fitzingerii species group - Grummer, Jared A. (2018)
Rapid evolutionary radiations are difficult to resolve because divergence events are nearly synchronous and gene flow among nascent species can be high, resulting in a phylogenetic “bush”. Large datasets composed of sequence loci from across the genome can potentially help resolve some of these difficult phylogenetic problems. A suitable test case is the Liolaemus fitzingerii species group of lizards, which includes twelve species that are broadly distributed in Argentinean Patagonia. The species in the group have had a complex evolutionary history that has led to high morphological variation and unstable taxonomy. We generated a sequence capture dataset for 28 ingroup individuals of 580 nuclear loci, alongside a mitogenomic dataset, to infer phylogenetic relationships among species in this group. Relationships among species were generally weakly supported with the nuclear data, and along with an inferred age of ∼2.6 million years old, indicate either rapid evolution, hybridization, incomplete lineage sorting, non-informative data, or a combination thereof. We inferred a signal of mito-nuclear discordance, indicating potential hybridization between L. melanops and L. martorii, and phylogenetic network analyses provided support for 5 reticulation events among species. Phasing the nuclear loci did not provide additional insight into relationships or suspected patterns of hybridization. Only one clade, composed of L. camarones, L. fitzingerii, and L. xanthoviridis was recovered across all analyses. Genomic datasets provide molecular systematists with new opportunities to resolve difficult phylogenetic problems, yet the lack of phylogenetic resolution in Patagonian Liolaemus is biologically meaningful and indicative of a recent and rapid evolutionary radiation. The phylogenetic relationships of the Liolaemus fitzingerii group may be best modeled as a reticulated network instead of a bifurcating phylogeny.